2020
DOI: 10.1002/14651858.cd010255.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Telerehabilitation services for stroke

Abstract: Cochrane Database of Systematic Reviews Data collection and analysisTwo review authors independently identified trials on the basis of prespecified inclusion criteria, extracted data and assessed risk of bias. A third review author moderated any disagreements. The review authors contacted investigators to ask for missing information. We used GRADE to assess the quality of the evidence and interpret findings. Main resultsWe included 22 trials in the review involving a total of 1937 participants. The studies ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
279
0
15

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 329 publications
(305 citation statements)
references
References 85 publications
11
279
0
15
Order By: Relevance
“…29,30 Strategies associated with telerehabilitation, such as phone calls, text messaging and video communications, are low-cost reasonable strategies that could help improve rates of adherence to exercises. 31,32 In addition, the results demonstrated that most demographic and clinical factors were not associated with adherence, which is in accordance with Dalcin et al 20 promote changes in self-awareness related to exercise practice, which could minimize the lack of interest, motivation, time, and tiredness. 29,30 Health education, provided by video animations and infographics, may inform about disease prognosis and benefits of exercises, which could minimize noncommitment and doubts regarding short-and long-term effects of exercises.…”
Section: Discussionsupporting
confidence: 85%
“…29,30 Strategies associated with telerehabilitation, such as phone calls, text messaging and video communications, are low-cost reasonable strategies that could help improve rates of adherence to exercises. 31,32 In addition, the results demonstrated that most demographic and clinical factors were not associated with adherence, which is in accordance with Dalcin et al 20 promote changes in self-awareness related to exercise practice, which could minimize the lack of interest, motivation, time, and tiredness. 29,30 Health education, provided by video animations and infographics, may inform about disease prognosis and benefits of exercises, which could minimize noncommitment and doubts regarding short-and long-term effects of exercises.…”
Section: Discussionsupporting
confidence: 85%
“…Telehealth is an alternative way to provide rehabilitation services. Technological advances prove to be a facilitator in the communication between the health professional and the patient especially in remote locations, presenting great potential as a substitute or as a complement to current therapies [23]. Digital practice is not a modality used in all countries and depends on the local regulations.…”
Section: Discussionmentioning
confidence: 99%
“…Telerehabilitation was initially aimed to improve motor outcomes, but the interest in the treatment of cognitive deficits has increased over the years. Studies ranged from pilot reports, (33), and multiple sclerosis (34). Telemedicine interventions were found not to be inferior to conventional face-to-face approaches in terms of efficacy, validity, reliability, and patients' satisfaction, but the low number of randomized controlled trials hampered definitive conclusions (35,36).…”
Section: Telemedicine and Telerehabilitation For Cognitive Disordersmentioning
confidence: 99%